Letter (copy) : International conference - Tracey, Herbert
021-0100-001 HTT/HT/769 Publicity February 24, 1937 Mr. Harold Outram The Associated Press, 20, Tudor Street, London, E.C.4 Dear Sir, INTERNATIONAL CONFERENCE. Your letter of the 23rd instant, addressed to Sir Walter Citrine, has been passed on to me. I think it will be possible to arrange for photographs during the International Conference on March 10 and 11. Arrangements are now being worked out, and I will keep your letter before me and communicate with you nearer the date of the Conference. Yours faithfully, Publicity Officer. 292/946/21/100